Pengaruh Motivasi Berprestasi dan Kompetensi Kepribadian Terhadap Kinerja Dosen Universitas Muhammadiyah Tangerang - Waluyo, Bambang Suhardi; Syarifuddin, Encep; Anriani, Nurul (Universitas Nusantara PGRI Kediri, 2023)
This study aims to examine the effect of achievement motivation on lecturer performance, examine the effect of personality competence on lecturer performance and examine the effect of achievement motivation and personality competence on lecturer performance. the subject of this research is a lecturer at the University of Muhammadiyah Tangerang. The research method used in this study is a quantitative descriptive method. The instruments used in this study were achievement motivation questionnaires, personality competency tests and lecturer performance questionnaires. The population in this study were 520 lecturers at the Muhammadiyah University of Tangerang. The sampling technique used in this study is saturated sampling method which takes the entire population as the research sample. The results of this study have found that there is an influence of achievement motivation on the performance of lecturers at the University of Muhammadiyah Tangerang, there is an influence of personality competence on the performance of lecturers at the University of Muhammadiyah Tangerang and there is an effect of achievement motivation and personality competence on the performance of lecturers at the University of Muhammadiyah Tangerang.